Pengaruh Word Of Mouth, Persepsi Risiko Dan Picturial Warning Terhadap Minat Beli Konsumen - Andri Lis One Ardhani; Putri Reno Kemala Sari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2021)
This study aimed to analyze the effect of word of mouth, risk perception, and pictorial warning on consumers buying interest in cigarettes in the Sumbawa Regency. This research used quantitative methods. The sample in this study was obtained using a non-probability sampling technique totaling 100 respondents. The data obtained were processed using SPSS version 16. The results in this study indicated that (1) the word of mouth variable has a significant effect on buying interest. (2) the risk perception variable does not affect and is not significant on buying interest. (3) the pictorial warning variable does not affect and is not significant on buying interest